2021
DOI: 10.1002/ajh.26388
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and cellular immune responses to recombinant herpes zoster vaccine in patients with chronic lymphocytic leukemia and monoclonal B cell lymphocytosis

Abstract: Monoclonal B-cell lymphocytosis (MBL) and chronic lymphocytic leukemia (CLL) are clonal B-cell disorders associated with an increased risk of infections and impaired vaccination responses. We investigated the immunogenicity of recombinant zoster vaccine (RZV) in these patients. Individuals with MBL/untreated CLL and Bruton tyrosine kinase inhibitor (BTKi)-treated CLL patients were given two doses of RZV separated by 2 months. Responses assessed at 3 and 12 months from the first dose of RZV by an anti-glycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…CMI plays a critical role in the protection of VZV reactivation. 22 Studies have reported COVID-19 infection can damage the function of CD4+ T cells, natural killer cells, and CD8+ T cells, which may potentially lead to HZ reactivation. 23 vaccines, and they demonstrated that mRNA induced higher neutralizing antibodies than inactivated vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…CMI plays a critical role in the protection of VZV reactivation. 22 Studies have reported COVID-19 infection can damage the function of CD4+ T cells, natural killer cells, and CD8+ T cells, which may potentially lead to HZ reactivation. 23 vaccines, and they demonstrated that mRNA induced higher neutralizing antibodies than inactivated vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the gp-ELISA has high sensitivity and specificity, and a high consistency with FAMA, and is thus considered to be the most likely alternative to FAMA [ 54 ]. In addition, GSK also developed an in-house ELISA to detect VZV gE antibody (gE-ELISA) and applied it to evaluating the immunogenicity of a herpes zoster subunit vaccine Shingrix [ 55 ].…”
Section: Methods For the Detection Of Anti-vzv Antibodiesmentioning
confidence: 99%
“…Impaired seroconversion was also reported after 13 and 23 valent Pneumococcus vaccine (PCV13 and PPV23) [ [58] , [59] , [60] ]. On the contrary, recombinant Varicella Zoster vaccine (rVZV) was associated with higher seroconversion rates (41 to 75%), although with lower responses in those receiving BTKi for longer period [ [61] , [62] , [63] , [64] ].…”
Section: Ibrutinib and Other Btk Inhibitorsmentioning
confidence: 99%